Analysis of Work System Design to Increase Production Productivity Using the MOST (Maynard Operation Sequence Technique) Method (Case Study of PT. Segar Murni Utama) - Ifan Wahyu Pranata Dewantara; Boy Isma Putra (Procedia of Engineering and Life Science, 2022)
PT. Segar Murni Utama is a company engaged in the mineral water industry, especially the production of MOJO TRAS demineralized water. PT. Segar Murni Utama introduces demineralized water products widely and is marketed among the general public to meet the needs of the community. This company prioritizes the quality of demineralized water very well.The purpose of this study was to optimize the production operator time for the cup section and optimize the packing process time for the cup section using the MOST (Maynard Operation Sequence of Technique) method. MOST (Maynard Operation Sequence Tecnique) is one of several ways of timing sub-operations or movements. The BEST method includes basic sort patterns.The results of this study in the cup production operator section showed that the right hand and left hand maps were known to have 8 activities, and 8 activities on the process flow map. The total time is 1410, the normal time (WN) is 0.85 minutes, the standard time (WS) is 0.017 hours, the standard output (OS) is 59 cartons/hour, and the final calculation result is 413 cartons/day. While the results of improvements in the packing cup section obtained the following results: Right hand and left hand maps are known to have 11 activities, and 11 activities on the process flow map. The total time is 2110, the normal time (WN) is 1.26 minutes, the standard time (WS) is 0.023 hours, the standard output (OS) is 43 cartons/hour, and the final calculation result is 301 cartons/day.